Kuasa Identitas Santri di TikTok - Malayati, Robi'ah Machtumah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
TikTok has become a social media platform that facilitates the dissemination of content from various groups, including pesantren (Islamic boarding schools). This study explores the power of santri (Islamic students) identity on TikTok through the account @hudzaa, which has 3.1 million followers and features content highlighting santri life, such as religious studies activities and distinctive pesantren symbols. Utilizing Tajfel and Turner's social identity theory and Bourdieu's concept of symbolic power, this research reveals how the santri identity on TikTok not only serves as a means of da'wah (Islamic preaching) but also acts as a form of power relations in the digital space. The @hudzaa account fosters strong interactions with Generation Z through creative content, thereby reinforcing the santri identity and creating influence in the digital social dynamics. This phenomenon reflects how pesantren adapt to technological advancements to assert religious authority in the social media era.